Pengaruh Monitoring Centre For Prevention Dan Inventarisasi Aset Terhadap Efektivitas Pemanfaatan Aset Tetap Pada Pemerintah Kabupaten Kediri - Kristanti, Dian; Hidayati, Nur (Universitas Islam Kadiri, 2024)
This research aims to analyze the influence of the monitoring center for prevention and asset inventory on the effectiveness of the utilization of fixed assets in the Kediri Regency government partially and simultaneously. This research is quantitative research. The population in this study was all goods administration officials and user goods administrators throughout Kediri Regency, totaling 134 people. The sampling technique used was the purposive sampling method. The total sample that will be used as respondents from each OPD in this research is 58 people. The sample criteria used in this research are goods administration officials and user goods administrators throughout Kediri Regency. The data analysis technique used is multiple linear regression analysis. The results of this research show that: 1) Monitoring Center for Prevention has a significant effect on the Effectiveness of Fixed Asset Utilization; 2) Asset Inventory has a significant effect on the Effectiveness of Fixed Asset Utilization; 3) Monitoring Center for Prevention and Asset Inventory simultaneously have a significant effect on the Effectiveness of Fixed Asset Utilization.